Emergence potential of sylvatic dengue virus type 4 in the urban transmission cycle is restrained by vaccination and homotypic immunity - Durbin, Anna P.; Mayer, Sandra V.; Rossi, Shannan L.; Amaya-Larios, Irma Y.; Ramos-Castaneda, Jose; Eng, Eong Ooi; Cardosa, M. Jane; Munoz-Jordan, Jorge L.; Tesh, Robert B.; Messer, William B.; Weaver, Scott C.; Vasilakis, Nikos (Academic Press Inc., 2013)
Sylvatic dengue viruses (DENV) are both evolutionarily and ecologically distinct from human DENV and are maintained in an enzootic transmission cycle. Evidence of sylvatic human infections from West Africa and Southeast Asia suggests that sylvatic DENV come into regular contact with humans. Thus, this potential of emergence into the human transmission cycle could limit the potential for eradicating this cycle with vaccines currently in late stages of development. We assessed the likelihood of sylvatic DENV-4 emergence in the face of natural immunity to current human strains and vaccination with two DENV-4 vaccine candidates. Our data indicate homotypic neutralization of sylvatic and human DENV-4 strains by human primary convalescent and vaccinee sera but limited heterotypic immunity. These results suggest that emergence of sylvatic strains into the human cycle would be limited by homotypic immunity mediated by virus neutralizing antibodies produced by natural infection or vaccination.